Kajian Penggunaan Daun Pisang Kering dalam Pematangan Buah Pisang (Musa Paradisiaca L CV. Kepok) dengan Metode Pemeraman di Lubang Tanah - Marhaen, Marhaen; Kusmiadi, Riwan; Ropalia, Ropalia (Penerbit Goodwood, 2023)
Purpose: This study aimed to examine the effect of dried banana leaves on the ripening process of kapok bananas and evaluate their impact on fruit quality. The research intended to determine whether adding different quantities of dried banana leaves could accelerate ripening, reduce post-harvest losses, and offer a natural, low-cost alternative to chemical ripening agents. Research Methodology: The research was conducted from May to June 2022 at the Agrotechnology Laboratory and Research and Experimental Garden, University of Bangka Belitung. A CRD was used with three treatments: bananas without dried leaves, bananas with 108 g/0.5 m³ of partially dried leaves, and bananas with 216 g/0.5 m³ of fully dried leaves. Each treatment was replicated six times, resulting in 18 experimental units. Observations were made on day 4 and day 6, measuring parameters such as ripening time, fruit hardness, total dissolved solids, vitamin C content, and weight loss. Results: The findings showed that adding dried banana leaves did not significantly affect the ripening time or the fruit quality parameters measured. All treatments reached ripening at the same time, and no substantial differences were observed in vitamin C content, fruit hardness, weight loss. Conclusion: Although dried banana leaves did not significantly speed up ripening, they can help maintain consistent fruit quality and reduce post-harvest losses. Limitations: The study was limited by its small sample size, short observation period, and focus on one banana variety. Contribution: This research offers preliminary evidence of dried banana leaves as a potential natural method for post-harvest banana ripening.